2000
DOI: 10.1038/sj.onc.1203416
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor competition between the ligand-bound oestrogen receptor and an intron 1 enhancer leads to oestrogen repression of ERBB2 expression in breast cancer

Abstract: Overexpression of the ERBB2 proto-oncogene in breast tumours, which occurs in 25 ± 30% of patients, correlates with poor prognosis. In oestrogen receptor (ER) positive breast epithelial cells oestrogens reduce ERBB2 mRNA and protein levels, an e ect that is reversed in the presence of anti-oestrogens such as tamoxifen and ICI 182780. Our previous studies have shown that the major e ect of oestrogen on ERBB2 expression is at the level of transcription and that this is mediated through a region within the ERBB2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 38 publications
3
57
1
Order By: Relevance
“…Another possibility is that other regulatory elements, located outside the promoter region tested in this study, could influence ERBB2 expression in colon and ovary cancer cells. For instance, sequences described in the first intron (Newman et al, 2000) or 12 kb upstream the conventional start site of the ERBB2 gene (Nezu et al, 1999) should be studied. We also have to keep in mind the multiple levels of erbB-2 mRNA and protein expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that other regulatory elements, located outside the promoter region tested in this study, could influence ERBB2 expression in colon and ovary cancer cells. For instance, sequences described in the first intron (Newman et al, 2000) or 12 kb upstream the conventional start site of the ERBB2 gene (Nezu et al, 1999) should be studied. We also have to keep in mind the multiple levels of erbB-2 mRNA and protein expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, tamoxifen-bound ESR1 recruits NCOR allowing ERBB2 transcription to be activated (Newman et al 2000). Hence, long-term treatment with tamoxifen could potentially lead to increased ERBB2 expression influencing the cellular localization of the ESR1.…”
Section: S Pancholi Et Al: Erbb2 Influences Localization Of Esr1mentioning
confidence: 99%
“…Estrogen administration to breast cancer cell lines results in transcriptional repression of ErbB2. Independent studies found the ErbB2 promoter to be suppressed by either estrogen-induced downregulation or sequestration of the AP-2 or SRC-1 transcription factors respectively (Newman et al, 2000;Perissi et al, 2000).…”
Section: Estrogen Represses Erbb2 Expression and Vice Versamentioning
confidence: 99%